Integrating vocational supports into a transition clinic: A pilot program - Elijah W. Hale; Aryn Taylor; Marlee Elton; Melanie Honsbruch; Cordelia Robinson Rosenberg; Jessica Solomon Sanders (Health Care Transitions)
Objective: Pilot a clinical model and study to learn more about how employment impacts health in children and young adults with intellectual and developmental disabilities. Background: As young individuals transition into adulthood, milestones such as independent living and gainful employment become paramount. However, for those with intellectual and developmental disabilities (IDD), these milestones can diverge notably from those of typically developing peers. They often confront distinct challenges, especially during shifts from pediatric to adult health care and transitioning from school to employment. Despite the positive influence of employment on quality of life, fragmented support systems create barriers to achieving this outcome. Employment is an important aspect of overall health and wellness, and more research is needed to determine how employment supports can be integrated with health care to improve certain health outcomes. Design: Self-determination theory and social ecological theory highlight the need for a comprehensive approach that considers both the internal needs and motivations of the individual with IDD and the external factors that influence their transition to adulthood. Based in these theories, our intervention offers an innovative blend of vocational support within a transition services framework at a large academic hospital. Our study introduces vocational support tailored for IDD youths within three health clinics. Results: Initial results demonstrate the technical and scheduling feasibility of integrating the intervention within existing healthcare services. The study has enrolled several participants, showing potential in technical, scheduling, economic, and operational domains. However, upcoming long-term data and comprehensive evaluation are required for a conclusive understanding of the intervention's impact. Conclusions: The program integrates vocational support into transitioning individuals with IDD from childhood to adult health care services. This intervention has potential to improve the health outcomes and quality of life for individuals with IDD, which could drive broader interdisciplinary interventions.